A Blind Approach to Joint Noise and Acoustic Echo Cancellation - Low, Siow Yong; Nordholm, Sven (Conference Management Services Pty Ltd, 2005)
This paper introduces a new scheme which combines the popular blind signal separation (BSS) and a post-processor to jointly suppress noise and acoustic echo. The new L element structure uses the BSS as a front-end processor to spatially extract the target signal from the interference (noise and echo). Statistical measures are then employed to select the target signal dominant signal from the BSS outputs. The remaining L − 1 BSS outputs (noise and echo dominant) and the existing far-end line echo are then used as the reference signals in an adaptive noise canceller (ANC) to temporally enhance the target signal. The novel structure bypasses the need for any a priori information whilst compensating the separation quality of the BSS temporally. Real room evaluations demonstrate the efficacy of the scheme in both noisy double-talk and non-double-talk situation.